Drawing Solution: Ekspresi Seni dalam Konseling Ringkas Berfokus Solusi - Saputra, Wahyu Nanda Eka; Wiretna, Claudy Desya; Utami, Sri Rahayu; Ramadhani, Annisa (STKIP Muhammadiyah Pringsewu, 2018)
The need for counseling services becomes urgent today. Focusing on the rapidity of counseled solutions becomes a counselor challenge in providing counseling services to counselees. One approach to counseling that addresses these challenges is the solution-focused brief counseling (SFBC). This approach is more important than solution talk rather than problem talk. One element that enhances the effectiveness of SFBC is the optimization of art expression by drawing solution. Art expressions with drawing solutions provide counselors with opportunities to describe solutions to their problems with intermediate exclusive questions and miracle questions techniques. This article will discuss the procedure of drawing a solution as a reference counselor to conduct counseling practice.Keywords:Â drawing solution, expressive art, solution-focused brief counseling.